2020
DOI: 10.3390/rs12050770
|View full text |Cite
|
Sign up to set email alerts
|

Performance Assessment of ICESat-2 Laser Altimeter Data for Water-Level Measurement over Lakes and Reservoirs in China

Abstract: Although the Advanced Topographic Laser Altimeter System (ATLAS) onboard the Ice, Cloud, and Land Elevation Satellite-2 (ICESat-2) was primarily designed for glacier and sea-ice measurement, it can also be applied to monitor lake surface height (LSH). However, its performance in monitoring lakes/reservoirs has rarely been assessed. Here, we report an accuracy evaluation of the ICESat-2 laser altimetry data over 30 reservoirs in China using gauge data. To show its characteristics in large-scale lake monitoring,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 39 publications
2
37
0
Order By: Relevance
“…In general, the results obtained from this investigation are similar to that of works done by Zhang et al and Yuan et al [6,7]. However the analysis carried out in our study using 15 reservoirs/water bodies, it appears that height retrieved from the strong beam is slightly better than that of height retrieved from the weak beams.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In general, the results obtained from this investigation are similar to that of works done by Zhang et al and Yuan et al [6,7]. However the analysis carried out in our study using 15 reservoirs/water bodies, it appears that height retrieved from the strong beam is slightly better than that of height retrieved from the weak beams.…”
Section: Discussionsupporting
confidence: 91%
“…Zhang et al used ICESat-2 ATL13 data for observing lake level and volume changes in Tibetan Plateau (where human activities are negligible) and concluded that the water surface height from ATL13 is in excellent agreement with in situ measurements for Qinghai Lake where the uncertainty is < 0.2 m [6]. Yuan et al have assessed the ICESat-2 ATL13 data product's accuracy in 30 reservoirs in China and their observation of mean relative errors was 0.06 m [7].…”
Section: Introductionmentioning
confidence: 99%
“…The root‐mean‐square error was 0.1 m, and 2 cm altimetric accuracy for one along‐track of ICESat‐2 for December 2018 (Zhang et al., 2019). ICESat‐2 also showed better agreement with in situ measurements for over 30 reservoirs in China (∼2 cm) than those of ICESat‐1 (∼7 cm) (Yuan et al., 2020). Over the ice sheet interior, the accuracy of ATL06 was better than 3 cm and the precision of surface measurements was better than 9 cm.…”
Section: Methodsmentioning
confidence: 90%
“…For example, Klotz et al., (2020) map individual waves along the ICESat‐2 track and infer wave spectra and wind speed. Others have explored wave detection in sea ice (Horvat et al., 2020), inland water monitoring (Ryan et al., 2020; Yuan et al., 2020), and bathymetry detection (Albright & Glennie, 2020; Armon et al., 2020). By demonstrating general agreement between independent data sources (Figure 1), our analysis indicates an important role for ICESat‐2 in observing ongoing sea‐level change.…”
Section: Discussionmentioning
confidence: 99%